2007
DOI: 10.1155/2007/705789
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Care Ontario Colonoscopy Standards: Standards and Evidentiary Base

Abstract: Colorectal cancer (CRC) is the most common cause of non-tobacco-related cancer deaths in Canadian men and women, accounting for 10% of all cancer deaths. An estimated 7800 men and women will be diagnosed with CRC, and 3250 will die from the disease in Ontario in 2007. Given that CRC incidence and mortality rates in Ontario are among the highest in the world, the best opportunity to reduce this burden of disease would be through screening. The present report describes the findings and recommendations of Cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
14
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 68 publications
(172 reference statements)
6
14
0
1
Order By: Relevance
“…Because the OEC is a new institution, comment on the potential for missed adenomas (and cancer) cannot be made at this time. However, the best reassurance in this circumstance would be the better than average adenoma detection rate of 25.47% of all patients and polyp detection rate of 46.11% in a population with an average patient age of 57.1 years (8,13,20). Similar to previous publications, the present study confirmed an increasing adenoma detection rate with advancing age ( Table 5).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Because the OEC is a new institution, comment on the potential for missed adenomas (and cancer) cannot be made at this time. However, the best reassurance in this circumstance would be the better than average adenoma detection rate of 25.47% of all patients and polyp detection rate of 46.11% in a population with an average patient age of 57.1 years (8,13,20). Similar to previous publications, the present study confirmed an increasing adenoma detection rate with advancing age ( Table 5).…”
Section: Discussionsupporting
confidence: 91%
“…The routine practice at the OEC is to intubate the terminal ileum to confirm cecal intubation, and photo documentation of the ileum and cecal pole results in a reproducible and formal proof of a complete examination. The 98.98% cecal intubation rates achieved at the OEC are at least comparable with previous studies of in-hospital and academic institution procedures (8).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations